Analisis Pengaruh Modal Intelektual Terhadap Kinerja Keuangan Dengan Pendekatan Berbasis Pasar (Studi Kasus pada Perusahaan Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024) - Oktavia, Mutiara Belkis; Puspitasari, Endah Yuni; Makhsun, Arif (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the effect of intellectual capital on financial performance with a market-based approach in technology sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. Intellectual capital in this study is measured using the Modified Value Added Intellectual Capital (MVAIC) model, while financial performance with a market-based approach is tested using the Tobin's Q ratio. This sample consists of 9 technology sector companies that meet the selection criteria. Data were analyzed using the EVIEWS 12 application with simple linear regression. Based on the partial test (T) results conducted in this study, Ha is accepted. This can be seen from the significance value of 0.0021
Keywords: Intellectual Capital; Financial Performance with Market-Based Approach; Modified Value Added Intellectual Capital (MVAIC); Tobin’s Q; Technology Sector Companies